David M. Lampton, The Three Faces of Chinese Power. Might, Money and Minds, Berkeley-Los Ángeles-Londres, University of California Press, 2008. - Correa López, Gabriela (Estudios de Asia y África, 2012)
David M. Lampton, The Three Faces of Chinese Power. Might, Money and Minds, Berkeley-Los Ángeles-Londres, University of California Press, 2008.